Analysis of Perception and Impact of Letter of Reprimand and Letter of Force on Tax Revenue (Case Study of Pamekasan Primary Tax Office) - Erfani, Novelia Intan; Andini, Isnani Yuli (Formosa Journal of Applied Sciences, 2024)
This study aims to determine how the perception and impact of warning and forced letters on tax revenue at the Pamekasan Primary Tax Service Office (KPP). This research uses qualitative research methods using case studies. Data collection techniques through observation, interviews and documentation. The research shows that Billing with a warning letter and a forced letter at KPP Pratama Pamekasan both have the aim of disbursing tax arrears, the difference is that a warning letter is an ordinary warning letter while a forced letter is a letter that has a legal basis and can be said to have legal force above the warning letter. If the taxpayer is still unable to pay his tax debt after the issuance of a forced letter, there will be follow-up from tax officials such as confiscation, auction, prevention and confiscation. The impact of the issuance of warning letters and forced letters can disburse tax arrears which will then increase tax revenue at KPP Pratama Pamekasan.